The clinical and radiographic evaluation of Allium sativum oil (garlic oil) in comparison with mineral trioxide aggregate in primary molar pulpotomy - Taraneh Faghihi; Roza Haghgoo; Fateme Taghizade; Mehrshad Zareiyan; Majid Mehran; Ghassem Ansari (Wolters Kluwer Medknow Publications, 2021)
Background: Mineral trioxide aggregate (MTA) is known as a common biomaterial for pulpotomy of primary molars, with limitation including high cost, difficult handling, and long setting time. This study was conducted to compare the clinical and radiographic success rate of Allium sativum oil and MTA in pulpotomy of primary molar teeth. Materials and Methods: This randomized, controlled, clinical trial was performed on a group of children with at least two symptom-free primary molars requiring pulpotomy. A total of 90 teeth were randomly assigned into two groups: After pulp amputation and hemostasis, Group I received MTA as medication in the pulp chamber and Group II received Allium sativum oil over the pulp stumps. Pulp chamber was then filled with reinforced ZOE paste (zinc oxide eugenol) and teeth were restored using stainless steel crowns. The follow-up scheme of 6, 12, and 18 months was set, and teeth evaluation was conducted by a calibrated pediatric dentist based on the modified criteria proposed by Zurn and Seale. The results were analyzed using the generalized estimating equation analysis with the P = 0.05 as the level of significance. Results: The clinical success rate was 100% in both groups after all follow-ups. The radiographic success rate was, however, 91.1% after 6.75. 6% after 12 and 18 months in Group II while it was 95.6% after 6, 91.1% after 12 and 18 months in Group I in those follow-up points. The difference between the two groups was not statistically significant. Conclusion: According to the results, Allium sativum oil has a high clinical and radiographic success rate comparable to those of MTA.